Clinical and testing protocols for the analysis of epidermal growth factor receptor mutations in East Asian patients with non-small cell lung cancer: A combined clinical-molecular pathological approach - Manuel Salto-Tellez (2018)
Background: Several randomized phase III studies in advanced stage non-small cell lung cancer (NSCLC) confirmed the superior response rate and progression-free survival of using epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor as first-line therapy compared with chemotherapy in patients with activating EGFR mutations. Despite the need for EGFR mutation tests to guide first-line therapy in East Asian NSCLC, there are no current standard clinical and testing protocols. Methods: A consensus meeting was held involving expert oncologists, pulmonologists, and pathologists to discuss the current status and variations in EGFR mutation testing of NSCLC across Asia and to recommend a standard clinical and laboratory testing approach for future use. Results: Currently, EGFR mutation tests are only routinely performed in some East Asian countries and medical centers. The consensus recommendation was to perform the test in all newly diagnosed patients with advanced stage nonsquamous lung cancer and some squamous patients with clinical features associated with higher prevalence of EGFR mutations. To increase the sensitivity and specificity of the EGFR mutation tests, tissue acquisition and pretest sample evaluation are important steps in addition to standardization of the EGFR mutation test methodology. Conclusion: A standardized EGFR mutation testing protocol is an essential step toward realization of personalized medicine in East Asian NSCLC treatment. © 2011 by the International Association for the Study of Lung Cancer.